SISTEM PENGEMBANGAN PERIKANAN IKAN TERBANG DI PELABUHAN PERIKANAN NUSANTARA TUAL - Yanto Anwar; Tri Wiji Nurani; Mulyono Sumitro Baskoro (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2019)
Flying fish eggs are one of the fisheries commodities that have important economic value in the waters of Tual City. Based on the Decree of the Minister of Maritime Affairs and Fisheries Number 69 of 2016 concerning the Plan for the Management of Flying Fish Fishery, several priority issues that are the problem of flying fish are; (1) fish resources and habitat; (2) social and economic; (3) governance. The flying fish fisheries management plan is expected to support policies in the management of flying fish and flying fish eggs in the Fisheries Management Region of the Republic of Indonesia. The purpose of this study is to analyze the system problem situation and build a model for the development of flying fish egg fisheries. This research method uses system approach. The four-step system approach starts from needs analysis, problem formulation, system identification and system modeling. The results showed that the root problems in flying fish egg fisheries were many ships that did not have permit documents, the availability of data on potential fish resources, the use of fishing gear that were considered environmentally unfriendly, low human resources, high fuel prices and access to capital for fishermen. The model of developing flying fish eggs consists of submodel use of environmentally friendly fishing gear and submodel of the development of flying fish egg fishing business. The problem of flying fish egg fisheries in Tual PPN can be solved by the solution of the use of environmentally friendly fishing gear for flying fish resources and the development of the fly fish egg fishing business.